The Peach Botany, Production and Uses - Layne, Desmond R (CABI, 2014)
Before the 19th century, many non-Asians believed that the peach originated from Persia ( modern-day Iran). Peach probably came to Persia from China along the silk trading routes in the 2nd or 3rd century BC. The Persian origin hypothesis was due, in part, to the fact that peaches were brought from Persia to Europe by the Roman army in the 1st century BC. Alphonse De Candolle in his ‘Origin of Cultivated Plants’ (1885, Appleton and Co., New York, pp. 221–229) contended that peach originated in China. In his tome, ‘The Peaches of New York’ (1917, J.B. Lyon Co., Albany), U.P. Hedrick made the same assertion. In fact, Chinese literature refers to peach more than 1000 years before it fi rst appeared in any European writings. There is documented evidence of peach cultivation in China for more than 3000 years ago.